Effects of acetylsalicylic acid on fresh weight pigment and protein content of bean leaf discs (Phaseolus Vulgaris L.) - Çanakçi, S (Akademiai Kiado, 2003)
The effects of 100, 250, and 500 ppm acetylsalicylic acid solutions treatments on weight alteration, pigment and protein amounts in discs from the primary leaves of one month old bean (Phaseolus vulgaris L.) seedlings produced under greenhouse conditions are presented. The experiments show that: 100 ppm ASA had no significant influence (P > 0.05) but 250 and 500 ppm ASA caused an increase on weight loss (P < 0.01); ASA at higher concentrations (250 and 500 ppm), generally, caused a decrease on pigment amounts (P < 0.05-P < 0.01) but 100 ppm ASA had no considerably significant influence on them (P > 0.05), none of the ASA treatments caused a statistically significant influence on carotenoid amount (P > 0.05); 100 and 250 ppm ASA treatments did not cause a significant influence on protein amount (P > 0.05), however 500 ppm ASA treatment caused an increase on protein injury (P < 0.05). Consequently, it is supposed that wet weight loss, pigment and protein injury have somewhat increased on leaf discs, depending on the toxic effect of high acetylsalicylic acid concentrations.
Keywords: acetylsalicylic acid; toxic; leaf discs